O comportamento judicante das câmaras municipais goianas no exercício do controle externo do Poder Executivo Municipal: análise dos reflexos das teses fixadas nos temas de repercussão geral nos 157 e 835 pelo Supremo Tribunal Federal - Silva, Thalita da Costa e (2022)
Grounded in the historical trajectory of the government administration control theme, as well as its importance in the management models undertaken in Brazil, it`s acknowledged that governance has an apparatus that better accompanies the achievement of accountability and fundamental rights to administrative probity, access to information and righteous governance. In light of this theoretical framework, external control emerges, in charge of accounting, financial, budgetary, operational and patrimonial inspection. Notably related to this control over the acts of Municipal Mayors, it appears that there was a transfiguration regarding the subjects heading their judgment and concerning the acts issued by them. This is due to the fact that, in August 2016, the issue was faced by the Federal Supreme Court (Extraordinary Appeals n°729.744/MG and n° 848.826/CE), which established the exclusive competence of the City Council to judge the management accounts of the Mayors, when they performed as an expense authorizing officer, with the Court of Auditors uniquely bearing the responsibility of issuing a prior opinion, and defined that the opinion will only generate effects after its acceptance by the Legislative Power. On these grounds, this current empirical research aimed to analyze what the consequences of this change of understanding in the external control of the municipalities of Goiás were. After gathering the data carried out with the TCM/GO and the municipal councils of Goiás, the outcomes indicated that a significant part of the chambers are not aware of this competence to judge management accounts, which was consecrated to them. Furthermore, it was found that in most cases the Chamber does not follow-up the unfavorable opinion issued by the TCM/GO and approves the accounts. It was also noted that after the publication of the above-mentioned theses, an increase in the pendency of cases awaiting judgment by the Chambers. In the scrutiny of the judgmental behavior of the Municipal Legislature, there was greater speed when it comes to government accounts, to the detriment of management accounts, which on the whole are archived, even with the TCM/GO opinion for the rejection. It was also noticed that the average time for processing the Mayors' accountability process in the Chambers is around 2 years and six months, which undoubtedly makes situations that would give rise to ineligibility innocuous, in view of the lack of prevalence of the opinion until the Chamber's manifestation. In brief, it is inferred that, whether by reviewing the literature or empirical data, there was a weakening of the role of the Court of Auditors, since it lost its autonomy of judgment and its opinion no longer prevails as far as the Chamber pronounces itself, which culminates in the weakness of accountability in public management and, hence, in governance.